Estado e neoliberalismo: o pensamento de Wolfgang Streeck e o caso brasileiro - Marra, Kariny Cruz Nogueira (2022)
The main objective of the present research was to analyze to what extent the ideal-typical notion of the debt State elaborated by Wolfgang Streeck, who focused on understanding the contours of the financial and fiscal crisis of current capitalism, applies to the Brazilian State after the Constitutional Amendment nº. 95. Specifically, we propose a bibliographic review regarding the foundations of the modern State from the perspective of budget and taxation, carrying out the hypothesis that these two vectors are also capable of explaining power relations. Understand the strengths and weaknesses of the theory from a deep mapping of the theory itself, but also of the theoretical, historical, economic and political contexts. Initially, from authors who have directly criticized the theory of crisis presented by Streeck, such as Jürgen Habermas, Adam Tooze (2017), Jerome Roos (2019), Melinda Cooper (2017) and others that can be used as a contrast, Mark Blyth (2017) for example, we hypothesized that public debt is not an independent variable, as suggested. In fact, indebtedness has always been part of the fiscal policy of states, playing a relevant role, including in the evolution of capitalist states (ROOS, 2019). Thus, although it is evident that high public debt rates had relevant consequences for the world after 2008, it is not an intrinsic problem, much less the determining factor or condition for the democratic problems that followed. For this reason, with regard to the Brazilian case, the thesis presented by Streeck is unable to explain the contours of the country's fiscal and political situation, since Streeck ignores a central aspect of the dynamics between debt creditors and the State. It is not merely an economic issue, in which there is a growing debt that needs to be paid by a debtor who finds it increasingly difficult to pay off his debts, but it is a political issue. The peculiar situation in which Brazil finds itself, with regard to its public finances, in view of the extreme austerity measures that have been applied in the country, cannot be explained by the conception of the Debt State, or by the confrontation of Staatsvolk by the Marktvolk.